HPA axis function in alcohol use disorder: A systematic review and meta-analysis - Dunne, Neil; Ivers, Jo-Hanna (My University, 2023)
Alcohol use disorder (AUD) is a culturally pervasive and often treatment resistant disorder. Stress is a major trigger for relapse in AUD. Allostasis in response to stress is governed by the hypothalamic-pituitary-adrenal axis (HPA axis). Investigation into HPA axis functioning in response to stress in AUD may provide a novel drug target for AUD treatment. This systematic review found 46 studies concerning ongoing AUD, withdrawal from alcohol, early-abstinence (<6 months), and late- abstinence (>6 months). Cortisol responses were mixed in ongoing AUD and higher in withdrawal. In early abstinence, significantly lower responses to stress compared to healthy controls were found for ACTH (SMD = -1.47, p = < .001, I2: 35.68%) and cortisol (SMD = 1.32, p = < .001, I2: 38.97%). Baseline values did not significantly differ compared to healthy controls for ACTH (SMD = 0.39, p = < .001, I2: 81.11%) and cortisol (SMD = 0.74, p = .015, I2: 88.66%). HPA axis functionality may normalise following 6 months of abstinence, though this may be confounded by selection bias. HPA axis hypoactivity was associated with a higher risk of relapse. Future research should aim to investigate all sexes and races, increase methodological consistency and participant follow up, and use HPA-sensitising drugs during early abstinence to assess their effects on relapse rates. Overall, the HPA axis presents strong potential as a novel treatment target in AUD.
Keywords: Neuroscience; ADDICTION; ALCOHOL; ALCOHOL DEPENDENCE; HYPOTHALAMICO-PITUITARY-ADRENAL (HPA) AXIS; Neuroscience; Chronic Health Condition; Mental Health/Psychosocial disability